Quinolone Antimicrobial Agents - Hooper, David C; Ed. Wolfson, John S; Ed (American Society for Microbiology, 1993)
Quinolones remain the most important class of antimicrobial agents discovered in recent years - over 1000 have been synthesized and evaluated. This revised edition consolidates and updates current knowledge of quinolones, and contains 13 new chapters.